Performance analysis of desalination system working on humidification-dehumidification coupled with solar assisted air heater and wind tower: Closed and open water cycle. (15th July 2020) - Sachdev, Taranjeet; Gaba, Vivek Kumar; Tiwari, Anil Kr.
Highlights: Combination of wind tower with solar humidification dehumidification desalination system. Thermal comfort and production of potable water together. Conservation of energy and water both. Numerical analysis for time dependent behavior. Humidification and de-humidification for closed and open water cycle. Abstract: The world which is hot and arid strives for fresh water and thermal comfort, thus there are two basic requirements. In this work, performance of wind tower in combination with solar air heater assisted humidification-dehumidification desalination system working with closed and open air water cycle is analysed numerically for cooling effect and fresh water production. The behaviour of system has been studied by different air flow rate in tower, temperature drop due to energy stored in wall and clay conduits, temperature drop due to evaporative cooling, humidity of moist air available for cooling, amount of potable water produced in dehumidifier and its variation with design and operating variables. A mathematical model based on fluid flow, heat transfer, energy and mass balance in components of system has been developed. Study reveals that comfort condition is achieved mainly by evaporative cooling in wind tower. Optimized column height is found as 8–9 m suitable to design the wind tower with 65% decrease in air velocity, 31% decrease in air temperatures and change in relative humidity up to 90%, however 42% reduction in water requirement in humidifier is also achieved at 5 m height with a cooling effect of 3.5 kW. Air mass flow rate of 0.032–0.035 kg/sec in solar air heater found suitable with maximum productivity of 5 and 4.2 kg/day for closed and open water cycle respectively. Water mass flow rate of 0.035–0.038 kg/sec in dehumidifier has been found suitable for 200% increase in productivity.